PyCrystalSCD: um software para obtenção da demarcação do cluster supramolecular em cristais orgânicos - Xavier, Rodrigo Nóbrega Rocha (2020)
The supramolecular cluster, according to an approach proposed by the NUQUIMHE research group, is composed by a central molecule (M1) and the MN molecules around it, being the smallest portion of a crystal structure capable of providing all the topological and energetic information that characterize the intermolecular interactions involved throughout the entire crystal lattice. Correct identification of the supramolecular cluster is the starting point to understand the formation of a certain crystalline phase, which has extensive applicability. However, this is a very slow and fault-prone procedure when performed manually with the support of existing programs. In this work, the creation of the PyCrystalSCD software is reported, which is responsible for automating the most laborious part of that approach, which is the demarcation of the supramolecular cluster by obtaining the contact area between the involved molecules, using 3D Voronoi diagrams, in addition to generating files used in later stages of crystal analysis. The final code was 88 times faster than the manual procedure to perform a comparison dataset.